EU-US trade structure and risks - Luke Daly; Martina Lawless (The Economic and Social Research Institute (ESRI), 2021)
This paper maps out the trade relationship in goods between the two largest trading blocs in the global economy - the EU and US. We use detailed product category information to provide an in-depth description of current trade flows between the two markets, with a particular focus on how Irish-US trade patterns compare to those of the EU overall. Along with the overall size of the trade flows, we highlight the extent of diversification in terms of the number of products particularly dependant on the US market. We then examine the structure of current bilateral tariff rates and how these vary across product types. This is done at the most granular level possible, using the product level trade flows compiled by the United Nations and matching them to current tariff levels. This structure is then used to assess potential changes proposed to these tariffs, using the US June 2020 tariff announcement and EU retaliation as illustrations.
Keywords: 330; Außenhandelsstruktur; Zoll; Zollpolitik; Wirkungsanalyse; Schätzung; Internationale Wirtschaftsbeziehungen; EU-Staaten; USA; Vergleich; Irland